6 - L’adoption du « système LMD » par les universités du Cameroun : enjeux, contraintes et perspectives - Yves Bertrand Djouda Feudjio (Journal of Higher Education in Africa, 2009)
The BMD system currently poses important challenges to the international academic community. It marks a real progress of the internationalization and globalization of higher education. The effective adoption of the Bologna Process, however, looks very difficult for African universities which are “unprepared”, and still dominated by precarious structural conditions. A sociological diagnosis of the universities in Cameroon shows that despite the political willingness and the enthusiasm of academic officials, the adoption of the BMD model appears to be very “premature.” The Cameroonian academic environment remains “fragmented” and precarious, dominated by a political indoctrination of academic freedom. A fair and effective adoption of the BMD system in Cameroon must be preceded by an essential “academic purification”. A poor adoption of the BMD model could possibly lead to the subjection and weakening of Higher Education in Cameroon and across Africa.